Pengaruh Regulasi, Politik Anggaran, Perencanaan Anggaran, Sumber Daya Manusia Dan Pengadaan Barang/ Jasa Terhadap Penyerapan Anggaran Belanja Pada OPD Provinsi Sumatera Barat - Rifka Ramadhani; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to prove empirically the effect of regulation, budget politics, budget planning, human resources and the procurement of goods/services on budget absorption. This research is classified as causative research. The population in this study are 39 Regional Organizations (OPD) of West Sumatra Province. The sample in this study used the Total Sampling method. The type of data used in this study is primary and secondary data. Data collection techniques using a questionnaire consisting of 4 respondents in each OPD so that the questionnaire distributed was 156 questionnaires. The analytical method used is Multiple Regression Analysis using the SPSS version 25.00 program. The result of the study showed regulation, budget planning and the procurement of good/services has a significant positive effect on budget absorption. However, budget politics and human resources have no effect on budget absorption.